Iodinated Contrast Opacification Gradients in Normal Coronary Arteries Imaged with Prospectively ECG-Gated Single Heart Beat 320-Detector Row Computed Tomography - Steigner, Michael L. (2009)
BACKGROUND: To define and evaluate coronary contrast opacification gradients using prospectively ECG-gated single heart beat 320-detector row coronary angiography (CTA). METHODS AND RESULTS: Thirty-six patients with normal coronary arteries determined by 320 × 0.5 mm detector row coronary CTA were retrospectively evaluated with customized image post-processing software to measure Hounsfield Units (HU) at 1 mm intervals orthogonal to the artery center line. Linear regression determined correlation between mean HU and distance from the coronary ostium (regression slope defined as the distance gradient G(d)), lumen cross-sectional area (G(a)), and lumen short axis diameter (G(s)). For each gradient, differences between the three coronary arteries were analyzed with ANOVA. Linear regression determined correlations between measured gradients, heart rate, body-mass index (BMI), and cardiac phase. To determine feasibility in lesions, all three gradients were evaluated in 22 consecutive patients with left anterior descending artery lesions greater than or equal to 50% stenosis. For all 3 coronary arteries in all patients, the gradients G(a) and G(s) were significantly different from zero (p<0.0001), highly linear (Pearson r values 0.77-0.84), and had no significant difference between the LAD, LCx, and RCA (p>0.503). The distance gradient G(d) demonstrated nonlinearities in a small number of vessels and was significantly smaller in the RCA when compared to the left coronary system (p<0.001). Gradient variations between cardiac phases, heart rates, BMI, and readers were low. Gradients in patients with lesions were significantly different (p<0.021) than in patients considered normal by CTA. CONCLUSIONS: Measurement of contrast opacification gradients from temporally uniform coronary CTA demonstrates feasibility and reproducibility in patients with normal coronary arteries. For all patients the gradients defined with respect to the coronary lumen cross-sectional area and short axis diameters are highly linear, not significantly influenced by the coronary artery (LAD vs LCx vs RCA), and have only small variation with respect to patient parameters. Preliminary evaluation of gradients across coronary artery lesions is promising but requires additional study.